2016
DOI: 10.1016/j.actamat.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of free volumes in a metallic glass through Xe-ion irradiation

Abstract: The origin of the deformation in metallic glasses is attributed to rearrangements of atoms in some structurally weak spots behaving as flow units, which are associated with free volumes. In the present study, Xe-ion beam is used to manipulate the free-volume fraction, and influence on the mechanical behavior of a Zr-based metallic glass. The irradiation at low dosages can change the structure by increasing the free volume, and by homogenising the distribution of free volume. The increase in the free-volume fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(47 citation statements)
references
References 78 publications
7
37
0
2
Order By: Relevance
“…7(a). This is because the He + ion irradiation led to an increased fraction of free volume and caused the extra atomic scale defects [9]. The crystalline regions showed that the peak-load increased as the dose increased from 2.5 × 10 17 ions/cm 2 to 1.0 × 10 18 ions/cm 2 in Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…7(a). This is because the He + ion irradiation led to an increased fraction of free volume and caused the extra atomic scale defects [9]. The crystalline regions showed that the peak-load increased as the dose increased from 2.5 × 10 17 ions/cm 2 to 1.0 × 10 18 ions/cm 2 in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Some studies have found that the ion beam resistance capability of the BMGs is greater than the traditional radiation resistance materials [8]. The free volume increases inside the matrix when a high irradiation dose is applied, which could improve the plastic-deformation ability and display a softening effect [9]. However, the BMGs usually failed due to catastrophic fracture, where they exhibit little macro plasticity at room temperature [10].…”
Section: Introductionmentioning
confidence: 99%
“…For BMGs, due to the lack of crystalline defects, the yield strength of BMGs is believed to be directly associated with the cohesive strength between atomic clusters343536. Furthermore, the yield strength is associated with the size of the elementary deformation units3037. The increase of elastic stress causes the atomic-bond anisotropic reorientation in the first nearest-neighbor shell, and then induces surrounding atoms shift concordantly, i.e., the atomic bonds elastically stretching (or shrinking) in other atomic shells113738.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the influences of cryogenic temperature and strain rate on the deformation behavior of BMGs were discussed in the framework of deformation kinetics22. In these work, shear band92324252627, serrated flows282930, activation energy of shear banding31 etc. have been comprehensively investigated.…”
mentioning
confidence: 99%
“…Cubuk et al [7] also noticed this and attributed it to a possible size effect, emphasizing that ε y~2 .9% holds only for a macroscopic behavior. Besides the size effect [28][29][30][31][32][33][34], many other factors may also play a role for the variation of ε y , such as the processing history [35][36][37][38][39][40] and chemical heterogeneity [41,42].…”
mentioning
confidence: 99%